The Intensity of Playing Video Games Relates Positively to Working Memory Capacity: Cross-Sectional Study in Students of Faculty of Medicine at Sebelas Maret University Surakarta. - Palupi, Pratiwi Indah; Wiyono, Nanang; Probandari, Ari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: The increase of video game popularity has captured researchersâ attention to conduct studies on effects of video games. Studies on video game playing indicate positive effects in improvement of cognitive function, namely working memory. Working memory capacity is a basic concept in modern cognitive psychology which plays significant role in daily activity performance, both academically and professionally. This research aimed to determine the probability of relationship between the Intensity of Playing Video Game and Working Memory Capacity in Students of Faculty of Medicine at Sebelas Maret University. Methods: This research was an analytical observational study with cross-sectional approach, conducted in Faculty of Medicine of Sebelas Maret University, Surakarta. The sample consisted of 109 students and was performed by utilizing total sampling technique with the restriction of inclusion and exclusion criteria. All respondents were asked to fill questionnaires of Lie Scale Minnesota Multiphasic Personality Inventory (L-MMPI) in order to measure their honesty scale, Scale for the Assessment of Pathological Computer-Gaming (in German language: Skala zum Computerspielverhalten/CSV-S) to measure their intensity of playing video game, and Reading Span Test to measure their working memory capacity. This research applied analytical methods of chi-square and logistic regression test. Results: This research pointed out that there were 20 students (18.3%) who intensely play video games and have a high rate of working memory capacity. The data analysis of chi-square test indicated that p=0,000 with Odds Ratio 16,364. The data analysis of logistic regression test established that the intensity of playing video games is the most significant risk factor and variable toward working memory capacity. Conclusion: The intensity of playing video games relates positively to working memory capacity in Students of Faculty of Medicine at Sebelas Maret University. Keywords: duration, frequency, intensity, video games, working memory capacityÂ